Real-World Evidence on Levetiracetam-Induced Hypokalemia: An Active Comparator Cohort Study - Ohoud Almadani; Raseel Alroba; Almaha Alfakhri; Sumaya Almohareb; Turki Althunian; Adel A. Alrwisan (Adis, Springer Healthcare, 2024)
Abstract Background Levetiracetam is an anti-seizure medication (ASM) with an established safety profile. However, a potential safety signal of hypokalemia following levetiracetam use was published in the World Health Organization newsletter. Objective To investigate the possible causal association between the use of levetiracetam and the development of hypokalemia. Method This was a new-user, active-comparator retrospective cohort study using Real-world Evidence Research Network data at the Saudi Food and Drug Authority from 2016 to 2022. Adults (≥ 18 years old) with an incident prescription for either levetiracetam or carbamazepine were followed for up to 6 months from the prescription date. Hypokalemia was ascertained by using diagnostic code (i.e., E87.6) or by serum potassium level below 3.5 mmol/L. A Cox proportional hazards model, adjusted with stabilized inverse probability of treatment weight, was fitted to compare the hazard of hypokalemia between levetiracetam and carbamazepine exposed patients. Results A total of 8,982 patients entered the study cohort. The incidence rate of hypokalemia was 303 cases per 10,000 patient-years in the levetiracetam-exposed cohort compared to 57 cases per 10,000 patient-years among carbamazepine users. Compared to carbamazepine users, patients exposed to levetiracetam had an adjusted hazard ratio related to induced hypokalemia of 1.99 (95% confidence interval, 0.88-4.49). Results of sensitivity analyses were comparable to the main analysis. Conclusion The hazard ratio for hypokalemia with the use of levetiracetam versus carbamazepine was statistically comparable. However, the potential association between levetiracetam use and hypokalemia cannot be ruled out given the elevated hazard ratios from the main and sensitivity analyses. Further studies may provide a more precise assessment of this association.